Hutsulshchyna and Public Progress - Kibych, Anna (Bulletin of Geography. Socio-economic Series, 2010)
The article describes the public-demographic changes in Hutsulshchyna in the light of political and economic surroundings of a changing Ukraine. There are indications proving that structural shifts in Hutsuls' ethnic culture, caused by cultural globalization, are about to happen. Preservation of ethnographic features in present-day conditions, as well as Hutsuls' adaptation to new social realities, appears to become a complex socio-cultural problem of this region of Ukraine.